The study on factors affecting the participation in the organization of the community tourism by farmer households in Tra Ving province, Vietnam - NGUYEN, Ha Hong (Journal of Economics Library, 2018)
Abstract. The study on the factors influencing farmer households’ participation in the organization of community-based tourism in Tra Vinh province was conducted by the gathering of primary data from 200 households in three islands of Tan Quy (Cau Ke district), Long Tri (Tra Vinh city), and Hoa Minh (Chau Thanh district) in Tra Vinh province. Through the use of the logistic regression model, the study found that there were six factors affecting the decision to participate in tourism, including the age of farmers, householders, and the educational level of householders, household size, family income, social relations and traditional trades. In particular, traditional trades, household income, and social relationships strongly influence farmers’ participation in organizing community-based tourism activities in Tra Vinh province. Keywords. Community tourism, Households, Island, Logistic regression, Income, Traditional trades. JEL. I13, I20, I30.